Nonlinear Finite Element Analysis of Flexural Laminated Veneer Lumber (LVL) Sengon Slender Beam - Mahmud Kori Effendi; Ali Awaludin (Institute of Research and Community Outreach - Petra Christian University, 2022)
Laminated Veneer Lumber (LVL) is one of the engineered wood products consisting of wood veneers that are glued and pressed together. In this study, the behavior of LVL Sengon slender beam is numerically investigated by means of nonlinear finite element analysis (FEA), where only half of the experimental beam was modeled due to symmetry of the load configuration. The LVL Sengon wood material used Hill failure criterion with isotropic hardening rules, and its mechanical properties in both tension and compression are modelled according to its mechanical properties in tension obtained from the clear specimen test. The contact analysis is defined for each contacting and contacted elements. The FEA results well agreed with the experimental results in term of the load-deflection curve and failure mode of the beam. It is found that the lateral support has no effect on the stiffness of the beam. The beam stiffness and ultimate load increase by the increase of beam height-to-width ratio (?/?).